2018
DOI: 10.1016/j.cortex.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic semantic cognition: Characterising coherent and controlled conceptual retrieval through time using magnetoencephalography and chronometric transcranial magnetic stimulation

Abstract: Distinct neural processes are thought to support the retrieval of semantic information that is (i) coherent with strongly-encoded aspects of knowledge, and (ii) non-dominant yet relevant for the current task or context. While the brain regions that support readily coherent and more controlled patterns of semantic retrieval are relatively well-characterised, the temporal dynamics of these processes are not well-understood. This study used magnetoencephalography (MEG) and dual-pulse chronometric transcranial mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
35
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 117 publications
(242 reference statements)
12
35
4
Order By: Relevance
“…By contrast, TMS to AG particularly disrupted the efficient retrieval of strong associations [71]. Our recent MEG results are consistent with this functional distinction within temporoparietal cortex [40,41]. pMTG showed a more substantial oscillatory response in weak association trials, while AG (along with ATL) showed a larger response to pairs of words that were linked by a strong association.…”
Section: Posterior Middle Temporal Gyrus and Angular Gyrus Fall Withisupporting
confidence: 84%
See 1 more Smart Citation
“…By contrast, TMS to AG particularly disrupted the efficient retrieval of strong associations [71]. Our recent MEG results are consistent with this functional distinction within temporoparietal cortex [40,41]. pMTG showed a more substantial oscillatory response in weak association trials, while AG (along with ATL) showed a larger response to pairs of words that were linked by a strong association.…”
Section: Posterior Middle Temporal Gyrus and Angular Gyrus Fall Withisupporting
confidence: 84%
“…Alternatively, manipulations of semantic control and judgements of thematic or event relations might rely on shared computational principles, explaining the similarity of largescale networks (beyond pMTG) that are implicated in these aspects of cognition [5,53]. We have suggested that pMTG might provide a dynamically updated conceptual 'context' which supports the tailored retrieval of currently relevant knowledge, even when this information is not the most strongly encoded within long-term memory [40]. This type of conceptual context would be expected to play a crucial role in the recovery of weakly instantiated knowledge that is important to the ongoing circumstances, but a less crucial role for dominant features or associations which are thought to be readily recovered within ATL without additional processing.…”
Section: How Can We Understand Functional Dissociations Within the Sementioning
confidence: 98%
“…To date, separate and complementary findings from a variety of time-resolved techniques provide partial and indirect support to the prediction made by the huband-spoke model. Chronometric TMSs and magnetoencephalography (MEG) findings indicate that ATL plays a crucial role in semantic processing 200-600 msec poststimulus onset (Teige et al, 2018;Jackson, Lambon Ralph, & Pobric, 2015;Lau, Gramfort, Hämäläinen, & Kuperberg, 2013). Although studies on the temporal features of word meaning access have traditionally focused on lateappearing ERPs, notably the N400 (Lau, Phillips, & Poeppel, 2008;Kutas & Federmeier, 2000), there is now evidence that semantic information is recovered much earlier in time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with damage on left IFG showed greater semantic deficits on similar tasks which require high executive control demands. These findings suggest that the prefrontal cortex is mainly associated with semantic control process (Corbett et al, 2009;Corbett, Jefferies, & Lambon Ralph, 2011;Jefferies, Patterson, & Ralph, 2008;Noonan et al, 2010;Novick, Kan, Trueswell, & Thompson-Schill, 2009;Soni et al, 2009;Teige et al, 2018).…”
Section: The Role Of Left Ifg In Chinese Semantic Cognitionmentioning
confidence: 74%
“…For example, left IFG activation largely increases when participants identify words with weak associations or accessing words with ambiguous meaning (Badre, Poldrack, Paré-Blagoev, Insler, & Wagner, 2005;Noppeney, Phillips, & Price, 2004;. These findings suggest that the prefrontal cortex is mainly associated with semantic control process (Corbett et al, 2009;Corbett, Jefferies, & Lambon Ralph, 2011;Jefferies, Patterson, & Ralph, 2008;Noonan et al, 2010;Novick, Kan, Trueswell, & Thompson-Schill, 2009;Soni et al, 2009;Teige et al, 2018). These findings suggest that the prefrontal cortex is mainly associated with semantic control process (Corbett et al, 2009;Corbett, Jefferies, & Lambon Ralph, 2011;Jefferies, Patterson, & Ralph, 2008;Noonan et al, 2010;Novick, Kan, Trueswell, & Thompson-Schill, 2009;Soni et al, 2009;Teige et al, 2018).…”
Section: The Role Of Left Ifg In Chinese Semantic Cognitionmentioning
confidence: 84%